Perceptions towards classroom participation: a case study of Malaysian undergraduate students - Mustapha, Siti Maziha; Nik Abdul Rahman, Nik Suryani; Mohd Yunus, Melor (Elsevier, 2010)
This paper aims to document perceptions that shape undergraduate students’ participation in Malaysian classrooms. On particular, it aims to discover students’ perception of classroom participation and how their perceptions impact their actual participation. Interviews and observations were carried out on a sample of 85 students from two communication classes. Results show that the multitude of views that students have on classroom participation signifies the unseen complex direct or indirect influence that impact their classroom participation patterns. Recommendations are offered to educators in formulating future teaching strategies that recognize students’ unique characteristics and promote open, supportive environment.